THE REALITY OF THE PRODUCTION OF FISH BREEDING FARMS IN THE CAGES CULTURE FLOATING IN THE PROVINCE OF THI QAR. - Jedran, Kareem K.; Hedroos, Tariq E.; Hamid, Qasir I. (Diyala Agricultural Sciences Journal, 2015)
This paper aims to evaluate and study the economic analysis of fish farming in the cages culture in the Thiqar province in the year of 2013. To get this purpose a sample of 8 farms used in this study، which cover 18% of the total approval farms in the province، the total number of approval farms equal to 44 farms subdivide into two groups، group one consists of 29 farms constructed on the Euphrates river، while the second group 15 farms constructed on the AlGarraf river. The economic analysis was carried out using 21 indicators after determine of the average values of the construction cost and incomes. The values of these indicators were determined on the base of one cage. The projects are success to contribute the national income through its total income which equal to 8404724، 7839093، 5933367، 6747096، 8661971، 9562612، 6548733، and 7034943 I.D، respectively. And the total income of total farms was equal to 7770214 I.D. whereas the construction cost was equal to 813099، 7691093، 581967، 6559596، 8306971، 9184300، 6353733، and 6634943 I.D، respectively. And for the total farms was equal to 7513984 I.D. This indicator shows the decrease of production investment of these projects. Therefore these projects in need of financial and technical support from government or supply the investors with the accessories and elements of production، which can expand these projects from the side and from other side، encourage the new investors to attend these projects. As well as the results showed that these projects presents a good employee of the available economic resources، it varies between1.586 – 2.067 to the farms، also the period of return the capital cost around 5.13 – 7.23 months، and as soon to the other indicators which proved that there are positive deviation on its values to all the farms which can encourage the investors to invest on these projects although the variation of the income and outcome cost due to local market conditions ، and the difference on the indicators values from farm to another farm because of the difference on the administrative skills.